# cosx(cos(x)-1)=0

## Simple and best practice solution for cosx(cos(x)-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cosx(cos(x)-1)=0 equation:

Simplifying
cosx(cos(x) + -1) = 0
Multiply cos * x
cosx(cosx + -1) = 0
Reorder the terms:
cosx(-1 + cosx) = 0
(-1 * cosx + cosx * cosx) = 0
(-1cosx + c2o2s2x2) = 0
Solving
-1cosx + c2o2s2x2 = 0
Solving for variable 'c'.
Factor out the Greatest Common Factor (GCF), 'cosx'.
cosx(-1 + cosx) = 0

#### Subproblem 1

Set the factor 'cosx' equal to zero and attempt to solve: Simplifying cosx = 0 Solving cosx = 0 Move all terms containing c to the left, all other terms to the right. Simplifying cosx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

#### Subproblem 2

Set the factor '(-1 + cosx)' equal to zero and attempt to solve: Simplifying -1 + cosx = 0 Solving -1 + cosx = 0 Move all terms containing c to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + cosx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + cosx = 0 + 1 cosx = 0 + 1 Combine like terms: 0 + 1 = 1 cosx = 1 Divide each side by 'osx'. c = o-1s-1x-1 Simplifying c = o-1s-1x-1

c = {o-1s-1x-1}